2022
DOI: 10.3390/ijerph19031769
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Dietary Patterns and Malnutrition, Low Muscle Mass and Sarcopenia in Adults with Cancer: A Scoping Review

Abstract: Dietary patterns examine the combinations, types and quantities of foods consumed in the diet. Compared to individual nutrients, dietary patterns may be better associated with cancer-related malnutrition, low muscle mass and sarcopenia. This scoping review identified associations between dietary patterns, assessed using data-driven methods (i.e., statistical methods used to derive existing dietary patterns) and hypothesis-orientated methods (i.e., adherence to diet quality indices), and malnutrition, low muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Most studies investigated the relationship between nutritional status and muscular dystrophy. Patients with colorectal cancer, as a common digestive tract tumor, are prone to malnutrition, which may be due to reduced intake, impaired digestive function, of nutrients and so on [21] .A study of elderly hospitalized patients in acute post-care reported that 15% of patients coexisted with malnutrition and sarcopenia [22], which was similar to our ndings. In a recent systematic review, 23% of hospitalized elderly patients coexisted with malnutrition and sarcopenia [23] .Beaudart et al [24] followed up the malnourished elderly in the community for four years and found that the risk of developing sarcopenia / severe sarcopenia (EWGSOP2) tripled during the follow-up period.…”
Section: Discussionsupporting
confidence: 88%
“…Most studies investigated the relationship between nutritional status and muscular dystrophy. Patients with colorectal cancer, as a common digestive tract tumor, are prone to malnutrition, which may be due to reduced intake, impaired digestive function, of nutrients and so on [21] .A study of elderly hospitalized patients in acute post-care reported that 15% of patients coexisted with malnutrition and sarcopenia [22], which was similar to our ndings. In a recent systematic review, 23% of hospitalized elderly patients coexisted with malnutrition and sarcopenia [23] .Beaudart et al [24] followed up the malnourished elderly in the community for four years and found that the risk of developing sarcopenia / severe sarcopenia (EWGSOP2) tripled during the follow-up period.…”
Section: Discussionsupporting
confidence: 88%
“…The approaches termed ‘any tolerated foods’, captured by the quote “any calorie is a good calorie”, or ‘foods beneficial for longer term health’ were both high-energy and high-protein recommendations, but varied significantly in regard to diet quality. One potential reason for this dichotomy of dietary approaches is a lack of evidence identifying the optimal dietary pattern(s) for people with cancer [ 22 ], and limited clear guidance as to which of these two approaches may be preferred during cancer treatment. As a result, oncology dietitians reported relying on long-standing beliefs around food intake, referring to knowledge from university (i.e., “… long-standing knowledge from uni days…”) to support food-specific recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…A ‘food-first’ approach is recommended to treat malnutrition; however, it remains unclear how dietitians implement this dietary approach in the clinical setting. With emerging evidence supporting a positive role for specific dietary patterns to support nutritional status and muscle health in cancer [ 13 , 22 ], it is essential to understand dietitians’ current practice and perception of dietary patterns to successfully integrate dietary patterns approaches into clinical practice. This study aimed to understand dietetic management of malnutrition and low muscle mass in the clinical oncology setting, focussing on food-specific recommendations, and to examine dietitians’ awareness and understanding of dietary patterns and barriers and enablers to their use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have examined the association between nutritional status and sarcopenia, particularly in patients with colorectal cancer (26). The presence of colorectal cancer increases the susceptibility to malnutrition, which can arise from various factors, including diminished dietary intake, compromised digestive function, and impaired nutrient absorption (27,28). A study conducted in elderly hospitalized patients during acute post-care revealed a coexistence rate of 15% for malnutrition and sarcopenia (29), which aligns with our own findings.…”
Section: Discussionmentioning
confidence: 99%